Mentosternal Contracture Reconstruction with ALT Free Flap, Z-Plasty, and Stsg: A Case Report - Chandra Wijaya Setiawan; Agus Roy Rusly Hariantana Hamid; I Gusti Putu Hendra Sanjaya; Gede Wara Samsarga; Shita Diwyani Sudarsa; Astrinita Lestari Suyata (GLOBAL HEALTH SCIENCE GROUP, 2024)
The consequences of post-burn neck contractures are considered the greatest challenge in reconstructive surgery. This deformity affects the neck area thereby limiting head movement. These complications can be associated with loss of articulation, cosmetic disfigurement and psychological changes that impair quality of life and result in loss of productivity. Therefore, an appropriate surgical management are essential to obtain optimal results. ALT (anterolateral) free flap can be used to resurface the defect, this technique provides a long pedicle with adequate lumen diameter of blood vessels. The z-plasty technique is useful for redirect a scar into better alignment with a natural skin fold or the lines of least skin tension. Split-thickness skin graft (STSG) is a preferred technique for large wound areas and relatively avascular sites. This study aims to report our experience in reconstructing burnt mentosternal contractures with ALT free flap, z-plasty and STSG. We present a clinical case of a thirty-five years old male with post-burn mentosternal contracture ONAH classification type III, dermogenic type diffuse flexion contracture of the colli region, anterior thorax region, and left and right superior extremity regions, dermogenic type linear contracture of the left and right anterior axillary regions, and burned ear deformity in the left and right auricular due to a history of burns from twenty-four years ago. A contracture release procedure was performed with ALT free flap reconstruction, z-plasty and STSG. After the reconstruction, a pleasing outcome was accomplished in terms of both functionality and esthetics. A severe mentosternal contracture was released, and the limited movement of the neck and both extremities was greatly lessened. Mentosternal contracture reconstruction with ALT free flap, z-plasty and STSG showed a good outcome in this case.